Preparation, structural and micromechanical properties of (Al/Mg) co-doped ZnO nanoparticles by sol–gel process - Asikuzun, E.; Ozturk, O.; Arda, L.; Akcan, D.; Senol, S. D.; Terzioglu, C. (Springer Science and Business Media LLC, 2015)
Zn0.90Mg0.10−xAlxO (x = 0.0, 0.1, 0.2, 0.3, 0.4, 0.5 and 0.10) nanoparticles were prepared by using sol–gel technique. The effects of Al and Mg doping on the structural and mechanical properties were investigated by using X-Ray diffraction (XRD), scanning electron microscopy (SEM) and digital micro-hardness tester, respectively. The grain size, a and c lattice parameters and morphology of nanoparticles were characterized by XRD and SEM measurements. The grain sizes of Al/Mg co-doped ZnO nanoparticles were also calculated by Scherrer–Warren equation. a and c lattice parameters are calculated from XRD peaks. According to the results it was observed that the grain sizes increased with increasing the Al doping. c lattice parameter partially decreased with Al doping. The experimental results of hardness measurements were analyzed using Meyer’s law, proportional specimen resistance model, elastic/plastic deformation model, and Hays–Kendall (HK) approach. It was observed that HK approach is the most successful model for the micro-hardness analysis of Al/Mg co-doped ZnO materials.
Keywords: Sol-Gel Process